Teacher Roles in Developing Emotional Intelligence of Preschool Children: Peran Guru dalam Mengembangkan Kecerdasan Emosional Anak Usia Dini - Nur Fatma Shafira; Evie Destiana (Academia Open, 2025)
General Background: Early childhood represents a critical developmental stage in which emotional intelligence forms the foundation for social adjustment, self-regulation, and interpersonal competence. Specific Background: In kindergarten settings, teachers function not only as instructors but also as daily role models who guide children’s emotional experiences through structured and habitual learning activities. Knowledge Gap: However, limited studies describe concretely how teacher roles are implemented in classroom practices to foster emotional intelligence among children aged 4–5 years. Aims: This study aims to describe the roles of teachers in building emotional intelligence at Dharma Wanita Persatuan Sedati Gede Kindergarten. Results: Using a descriptive qualitative design through observation, interviews, and documentation, findings indicate four integrated roles: educator through role-play activities, innovator through ice breaking and creative learning, communicator through storytelling and religious habituation, and motivator through daily routines such as queuing, sharing, praying, and classroom leadership. These practices support children in recognizing emotions, regulating behavior, showing empathy, and interacting confidently. Novelty: The study provides a contextual mapping of teacher functions linked directly to daily classroom strategies. Implications: The findings offer practical guidance for early childhood educators to structure consistent, meaningful activities that cultivate emotional intelligence in preschool environments. Keywords: Emotional Intelligence, Teacher Roles, Early Childhood Education, Classroom Practices, Preschool Learning Key Findings Highlights: Four functional positions guide socio-emotional growth in daily routines Experiential play activities stimulate empathy and self-control Religious habituation supports discipline and prosocial behavior